EVALUATION OF TOXIC HEAVY METALS IN AYURVEDIC SYRUPS SOLD IN LOCAL MARKETS OF HAZARA, PAKISTAN - Hajra, Bibi; Qayum, Iftikhar; Orakzai, Shaukat; Hussain, Fida; Faryal, Uzma; ., Aurangzeb (Journal of Ayub Medical College Abbottabad, 2015)
Background: Herbal and Ayurvedic preparations, widely used in Pakistanand the developing world, present serious risk of heavy metal toxicity related to their medicinal content and prolonged use by patients. The objective of this study was to find out the concentration of heavy metals in Herbal & Ayurvedic liquid preparations commonly used for treatment of different diseases, from local markets of Hazara. Methods: The cross sectional survey of traditional herbal & Ayurvedic medicine shops included ten liquid preparations selected from local shops of Mansehra and Abbottabad after interviewing the shopkeepers; so as to select the most commonly sold preparations along with their indications. All samples were analysed on standard Atomic Absorption Spectroscopy for qualitative and quantitative study of toxic heavy metals (Mercury, Iron, Zinc, Lead, Manganese and Arsenic). Results: Toxic levels of Mercury were present in seven syrups, i.e., (Kashneeze, Akseer e Pachas, Tankar, Sharbat e folad, Urosinal, Akseer e Jigar and Amrat dhara) while Arsenic was present only in Urosinal. Iron, Zinc, Manganese and Lead were present in permissible limits in all syrups. Conclusion: Mercury and Arsenic are present in local Herbal & Ayurvedic liquid preparations far beyond the permissible limits as proposed by the International Regulatory Authorities for health drugs while the rest of metals, i.e., Zinc, Manganese, and Iron are within the therapeutic limits. Keywords: Herbal bottle preparations, Heavy metal toxicity, Mercury, Arsenic, Atomic absorption spectrophotometer, Quality control